2021
DOI: 10.1021/acs.energyfuels.1c03818
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Study on Nitrogen Migration and Catalytic Denitrification during the Pyrolysis of Lysine and Tryptophan

Abstract: Catalytic fast pyrolysis can effectively solve the pollution and treatment problems of sewage sludge to realize the green recycling of biomass waste energy. The study on the mechanism of nitrogen migration is a crucial part of the conversion of sewage sludge. Herein, two amino acids of lysine with linear amines and tryptophan with aromatic nitrogen-containing heterocycles were used as typical model compounds to investigate the pyrolysis mechanism and nitrogen migration behavior. The results revealed that lysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…It was observed that the amine–N yield decreased slightly before 600 °C but then showed a sharp decrease by 15.57 wt % from 600 to 800 °C. This tendency of amine–N in tar was consistent with Zhao et al’s findings during the pyrolysis of some amino acids. The formation of amine–N can be attributed to the thermal cracking of more labile N–A in fuels .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It was observed that the amine–N yield decreased slightly before 600 °C but then showed a sharp decrease by 15.57 wt % from 600 to 800 °C. This tendency of amine–N in tar was consistent with Zhao et al’s findings during the pyrolysis of some amino acids. The formation of amine–N can be attributed to the thermal cracking of more labile N–A in fuels .…”
Section: Resultssupporting
confidence: 92%
“…As shown in Table S2, a large amount of N–heterocyclic compounds was found in tea waste pyrolysis tar, such as pyrrole, pyridine, indole, and their substitutes/derivatives. The discrepancy among these N–heterocyclic compounds mainly resulted from amino acids with different chemical structures. , As Zhao et al reported, lysine with linear amines was prone to form stable pyrrole and pyridine, while tryptophan with aromatic N–heterocycles was mainly converted into stable indole compounds. Heterocyclic–N increased with the temperature initially in both the Ar- and H 2 -rich atmospheres until 600 °C and then slowly declined to 20.91 wt % in an Ar atmosphere, while it shrank swiftly to 9.74 wt % in a H 2 -rich atmosphere at 800 °C.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the side chain of Trp is an indole group, which maintains stability at high temperatures. Consequently, Trp predominantly forms tryptamine, 1H-indole, and 3-methyl-1H-indole via decarboxylation (Pathway 3, Table S6 ) or deamination (Pathway 4, Table S6 ) during combustion 30 , 34 . Because the phenyl ring side chain of Phe also remains stable during combustion, it primarily degrades through two pathways: direct decarboxylation to form benzeneethanamine, and simultaneous removal of the amino and carboxyl groups to produce toluene 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Deamination is a condensation reaction that involves the formation of ammonia through the condensation of an amino group with a hydrogen atom. 42 This reaction has been observed in amino acids such as L-glutamine, L-glycine, and L-arginine. 36 Both reactions result in the formation of volatile compounds with low molecular weight, namely water and ammonia.…”
Section: Introductionmentioning
confidence: 95%
“…This reaction has been observed in amino acids such as l ‐histidine, l ‐arginine, and l ‐aspartic acid during thermal degradation. Deamination is a condensation reaction that involves the formation of ammonia through the condensation of an amino group with a hydrogen atom 42 . This reaction has been observed in amino acids such as l ‐glutamine, l ‐glycine, and l ‐arginine 36 .…”
Section: Introductionmentioning
confidence: 99%